2016
DOI: 10.1590/s0102-865020160050000009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the renal aging in rats. Stereological study

Abstract: Brazil. Scientific, intellectual, conception and design of the study; analysis and interpretation of data; statistics analysis; critical revision. ABSTRACT PURPOSE:To evaluate the renal function and the renal histological alterations through the stereology and morphometrics in rats submitted to the natural process of aging. METHODS:Seventy two Wistar rats, divided in six groups. Each group was sacrificed in a different age: 3, 6, 9, 12, 18 and 24 months.It was performed right nephrectomy, stereological and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
2
7
1
Order By: Relevance
“…The increase in the volume of the kidneys in older rats was apparently also marked by a decrease in renal function. (18) In contrast to the study results of Melchioretto et al (18) who state that increases in the volume of the kidneys are observable in rats from the age of 12 months, our study showed a peak increase in the weight of the kidneys occurring at the ages of 8 months (32 weeks) and 12 months (48 weeks). This may be due to the differences in experimental animals used.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The increase in the volume of the kidneys in older rats was apparently also marked by a decrease in renal function. (18) In contrast to the study results of Melchioretto et al (18) who state that increases in the volume of the kidneys are observable in rats from the age of 12 months, our study showed a peak increase in the weight of the kidneys occurring at the ages of 8 months (32 weeks) and 12 months (48 weeks). This may be due to the differences in experimental animals used.…”
Section: Discussioncontrasting
confidence: 99%
“…(26) The results of our study showed increases in organ weight of the kidneys, liver, spleen and testes with increasing age. The increases in the weight of the kidneys, liver, and spleen in our study are in line with those of Caglar et al, (13) Kim et al (14) and Melchioretto et al (18) , which are the results of autopsies on humans. The increases in the weight of the kidneys, liver, and spleen occurred concomitantly with increases in individual body weight and body mass index (BMI).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations